Venom On-a-Chip: A Fast and Efficient Method for Comparative Venomics - Zancolli, Giulia (Toxins (Basel), 2017)
Venom research has attracted an increasing interest in disparate fields, from drug development and pharmacology, to evolutionary biology and ecology, and rational antivenom production. Advances in “-omics” technologies have allowed the characterization of an increasing number of animal venoms, but the methodology currently available is suboptimal for large-scale comparisons of venom profiles. Here, we describe a fast, reproducible and semi-automated protocol for investigating snake venom variability, especially at the intraspecific level, using the Agilent Bioanalyzer on-chip technology. Our protocol generated a phenotype matrix which can be used for robust statistical analysis and correlations of venom variation with ecological correlates, or other extrinsic factors. We also demonstrate the ease and utility of combining on-chip technology with previously fractionated venoms for detection of specific individual toxin proteins. Our study describes a novel strategy for rapid venom discrimination and analysis of compositional variation at multiple taxonomic levels, allowing researchers to tackle evolutionary questions and unveiling the drivers of the incredible biodiversity of venoms.